Association of hOGG1 Ser326Cys, ITGA2 C807T, TNF-A -308G>A and XPD Lys751Gln polymorphisms with the survival of Malaysian NPC patients. - Eng-Zhuan Ban; Munn-Sann Lye; Pei Pei Chong; Yoke-Yeow Yap; Siew Ying Crystale Lim; Hejar Abdul Rahman (PLoS ONE)
Background Nasopharyngeal carcinoma is a rare form of cancer across the world except in certain areas such as Southern China, Hong Kong and Malaysia. NPC is considered a relatively radiosensitive tumor and patients diagnosed at early stages tend to survive longer compared to those with advanced disease. Given that early symptoms of NPC are non-specific and that the nasopharynx is relatively inaccessible, less invasive screening methods such as biomarker screening might be the key to improve NPC survival and management. A number of genes with their respective polymorphisms have been shown in past studies to be associated with survival of various cancers. hOGG1 and XPD genes encode for a DNA glycosylase and a DNA helicase respectively; both are proteins that are involved in DNA repair. ITGA2 is the alpha subunit of the transmembrane receptor integrin and is mainly responsible for cell-cell and cell-extracellular matrix interaction. TNF-α is a cytokine that is released by immune cells during inflammation. Methods Restriction fragment length polymorphism-polymerase chain reaction (RFLP-PCR) was used to genotype all the aforementioned gene polymorphisms. Kaplan-Meier survival function, log-rank test and Cox regression were used to investigate the effect of gene polymorphisms on the all-cause survival of NPC. Results NPC cases carrying T/T genotype of ITGA2 C807T have poorer all-cause survival compared to those with C/C genotypes, with an adjusted HR of 2.06 (95% CI = 1.14-3.72) in individual model. The 5-year survival rate of C/C carriers was 55% compared to those with C/T and T/T where the survival rates were 50% and 43%, respectively. Conclusion The finding from the present study showed that ITGA2 C807T polymorphism could be potentially useful as a prognostic biomarker for NPC. However, the prognostic value of ITGA2 C807T polymorphism has to be validated by well-designed further studies with larger patient numbers.